A Comparative Discourse Analysis of Mehdi Akhavān-Sāles’ Defense of the Poetic Style of Nimā Yūshij - Kulthum Miriasl (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This article aims to indicate how Akhavān-Sāles- the greatest defender of Nimāei poetry- introduced Nimāei poetry as the superior poetry and norm against the rival and sometimes contradictory poetic currents of his period. Our approach is based on the theory of discourse analysis by Laclau and Mouffe. By analyzing how discourses are articulated in literary works, we examine the influence of broader social, political, and cultural elements on the creation and reception of literature. This approach will enrich our understanding of critical literary works and demonstrate the power of interdisciplinary research to provide a deeper understanding of the social and political contexts that influence literary texts. The results show that Akhavān, with his mastery and sufficient knowledge of Persian poetry and a tendency towards socially committed literature, deconstructed and rejected other poetic discourses by expressing their structural (aesthetics) and content flaws. By introducing Nimā’s method as a mythical approach, free from other poetic discourses’ defects and shortcomings, Akhavān endeavored to convince Nimā’s opponents and revealed the superiority of his poetic style and its distinction from other poetic currents. Akhavān’s embracing of classical poetry and thought and his attempt to adapt the intellectual and formal themes and roots of Nimā’s innovations with classical poetry’s style is the secret of his success in reconciling the traditional and modern thought in the world of poetry.